IMPACT OF DIFFERENT CARDIOTONIC AGENTS ON MYOCARDIAL FUNCTION AFTER CORONARY ARTERY BYPASS GRAFTING - Akhmadaliev Shokhrukh Shukhratovich; Yusupov Anvar Sabirdjanovich (Modern American Journals, 2025)
Background: Postoperative myocardial dysfunction and low cardiac output syndrome (LCOS) remain among the most serious complications following coronary artery bypass grafting (CABG), significantly increasing morbidity, length of intensive care unit (ICU) stay, and early mortality. Optimal cardiotonic support is therefore crucial in the early postoperative period. Objective: To compare the effects of different cardiotonic agents on myocardial function, hemodynamics, and early clinical outcomes in patients after CABG. Methods: A prospective comparative study was conducted from 2022 to 2025 at the Republican Specialized Scientific and Practical Medical Center of Cardiology, Fergana Regional Branch. A total of 180 patients who developed LCOS after CABG were enrolled and divided into three groups receiving dobutamine, milrinone, or levosimendan. Echocardiographic, hemodynamic, and metabolic parameters were assessed.